The Impact of Cost Management Practices on Firm Profitability of Sri Lankan Manufacturing Companies during the COVID-19 - Mohamed Saleem Ahamed Riyad Rooly; Subaideen Issath Nimsith; Baiq El Badriati (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose: This study examines the effect of cost management practices on the profitability of listed manufacturing companies in Sri Lanka, focusing on the application of Activity-Based Costing (ABC) during the COVID-19 pandemic.Method: The study employs quantitative methods to analyze secondary data from the annual reports of 70 listed manufacturing companies between 2019 and 2023. Data analysis was conducted using SPSS software, including tests for correlation, multiple regression analysis, data stationarity, autocorrelation, and multicollinearity.Result: The findings reveal a significant negative correlation between direct material costs and profitability, suggesting that effective management of material costs through ABC enhances financial performance. Similarly, direct labor costs also show a significant negative relationship with profitability, emphasizing ABC's role in optimizing labor costs to increase profits. Factory overhead costs exhibit a significant negative correlation with profitability, highlighting ABC's effectiveness in reducing non-productive overheads. In contrast, administrative expenses have an insignificant impact on profitability, indicating the limited efficacy of ABC in managing these costs. Overall, the results affirm ABC's utility in controlling production-related costs but suggest the need for alternative strategies for managing administrative expenses.Practical Implications for Economic Growth and Development: The study emphasizes the importance of efficient cost reduction methods, which can improve firm productivity, increase profitability, and support stability and economic recovery in the post-pandemic period.